The supporting role of Schwann cells in perineural invasion of pancreatic ductal adenocarcinoma - He, Yun; Chen, Zheng; Yang, Liu; Qiao, Shuanying; Su, Zonghua; Ding, Feng; Ding, Fadian; Xin, Fuli; Xiang, Siyu; Lyu, Aiping; Li, Fangfei (Frontiers in Pharmacology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive cancer, with tumor cells readily disseminating to other organs through the bloodstream, lymphatic system, and nervous system, thereby impacting patients’ survival rates. PDAC is often associated with perineural invasion (PNI), which not only facilitates tumor spread but may also lead to symptoms such as pain, further affecting the patient’s quality of life. PNI is frequently observed in PDAC and has become an important histopathological marker associated with poor clinical outcomes. Many studies suggest that a high density of Schwann cells (SCs) is typically found in areas of PNI in PDAC. What’s more, as the primary glial cells in the PNS, SCs actively contribute to pancreatic tumour progression by releasing substances capable of interacting with cancer cells and promoting cancer cells proliferation and migration in tumor microenvironment (TME). Therefore, SCs are crucial in the interactions between nerves and tumors as the primary glial cells within PNS. In this review, our objective is to present novel insights and perspectives for PDAC therapy that targets SCs and related signal pathways to decrease PNI, thereby reduce pain and prolong survival in cancer patients. We detail and summarize the multiple mechanisms by which SCs promote PNI in tumors and thus lead to malignancy.